THE CONCEPT OF THE “EPILEPTIC SYSTEM” IS CREDITED TO RUSSIAN MEDICAL SCIENCE - V. A. Karlov (Эпилепсия и пароксизмальные состояния)
In the international literature, the nature of epileptogenesis is largely viewed through the relations between the epileptic focus and the nervous system. The Russian national neurophysiological and clinical science proposed the concept of pro- and anti-epileptic systems. The results of 50-year experimental and clinical studies fully confirmed this theory; some of the results are presented in this report. Among other aspects, for the first time, we explain why the avalanche of antiepileptic drugs in the pharmaceutical market cannot prevent the development of epileptic seizures resulted from the epileptic forms of brain damage.